2012
DOI: 10.1007/s00424-012-1143-6
|View full text |Cite
|
Sign up to set email alerts
|

Augmented intrarenal and urinary angiotensinogen in hypertension and chronic kidney disease

Abstract: Activated intrarenal renin–angiotensin system plays a cardinal role in the pathogenesis of hypertension and chronic kidney disease. Angiotensinogen is the only known substrate for renin, which is the rate-limiting enzyme of the renin–angiotensin system. Because the levels of angiotensinogen are close to the Michaelis–Menten constant values for renin, angiotensinogen levels as well as renin levels can control the renin–angiotensin system activity, and thus, upregulation of angiotensinogen leads to an increase i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
73
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 39 publications
(73 citation statements)
references
References 130 publications
0
73
0
Order By: Relevance
“…Indeed, previous studies have shown that the angiotensinogen gene plays a pivotal role in setting blood pressure levels and that angiotensinogen is involved in both intrarenal RAS activation and development of hypertension. 39, 40 Therefore, it is likely that training-induced angiotensinogen reduction in the renal artery is one important mechanism contributing to smaller vasoconstriction and blood pressure fall. Similar observations were previously made in trained vs. sedentary SHR: cardiovascular effects of Ang II were directly correlated with the reduction of Aogen mRNA expression in brain areas involved in cardiovascular control, 13 an effect similar to that observed after chronic losartan treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, previous studies have shown that the angiotensinogen gene plays a pivotal role in setting blood pressure levels and that angiotensinogen is involved in both intrarenal RAS activation and development of hypertension. 39, 40 Therefore, it is likely that training-induced angiotensinogen reduction in the renal artery is one important mechanism contributing to smaller vasoconstriction and blood pressure fall. Similar observations were previously made in trained vs. sedentary SHR: cardiovascular effects of Ang II were directly correlated with the reduction of Aogen mRNA expression in brain areas involved in cardiovascular control, 13 an effect similar to that observed after chronic losartan treatment.…”
Section: Discussionmentioning
confidence: 99%
“…An animal study shows that spironolactone treatment in animals with AKI reduces progression to CKD [92] . Elevated urinary angiotensinogen marks intrarenal RAS activation and CKD progression [93][94][95] . Animal studies show that intrarenal angiotensin II increases after renal ischemia reperfusion injury, while concentrations of angiotensin 1-7 (inhibitory molecule to angiotensin II) decrease in the kidney tissues [96] .…”
Section: Renin-angiotensin System Activationmentioning
confidence: 99%
“…While it is known that angiotensin II (Ang II) is the most powerful biologically active product of the RAS, recent studies have focused on the tissue-specific roles of this system [2,3]. Emerging evidence has demonstrated the importance of the RAS in brain, heart, adrenal glands, vasculature, and kidneys [4]. Angiotensin-converting enzyme (ACE) catalyzes the conversion of angiotensin I (Ang I) to Ang II [5].…”
Section: Introductionmentioning
confidence: 99%